Correlation Between Fracture Azimuth, Surface Lineaments and Regional Tectonics: A case study from Belik District, Central Java, Indonesia - Reza Syahputra; Felix Muria Hasudungan Sihombing; Octria Adi Prasojo (Journal of Geoscience, Engineering, Environment, and Technology, 2019)
Two major strike-slip faults with northeast-southwest and northwest-southeast orientation have shifted the southern Central Java, including Belik District. Consequently, many smaller faults that have the same direction as the major faults and west-east direction folding systems were emerged. The orientation of these geologic structures could be observed from morphological features such as ridge and river. A quantitative approach was carried out to unravel the impacts of those geologic structures on the geomorphology of the study area, which is located between Slamet Mountain and Sindoro Mountain, Central Java province. The method used in this research was the structural geology analysis, including the interpretation of ridge and river lineament, the distribution of fractures, and statistical analysis. The research location is divided into four different segments based on its lineament and morphology. The lineament that has similar characteristics was tested using normality test of Kolmogorov-Smirnov. The Spearman test was used to obtain the correlation between surface lineament and fracture azimuth. All fracture azimuth, ridges and rivers tend to have northwest-southeast and northeast-southwest direction. These results show similar direction with strike-slip regional structural pattern. The statistical calculation and field observation indicate the influence of external factor on the change of the study area’s landform.